Pola Manajemen Pembelajaran Bahasa Arab Integratif di Pesantren: (Studi Kasus Pesantren Muwahidun Putri-Pati) - Mahfuz Abdul Rajak (TARQIYAH: Jurnal Pendidikan dan Literasi, 2025)
Pesantren Muwahidun follows a modern pesantren system with an integrative learning approach. This study aimed to describe the integrative Arabic language learning management pattern at Pesantren Muwahidun Putri in Gembong-Pati. This study used a qualitative descriptive research method with a case study approach, collecting primary and secondary data through observations, interviews, documents, and audio-visual materials. The study's findings suggest an integrated approach to Arabic language learning at the Muwahidun Putri Integrated institution, encompassing both the Islamic boarding school and the general school. With its management pattern: 1. Program planning for integrated Arabic language learning is systematic and structured. 2. The organization of integrated Arabic language learning involves coordination between Pesantren and regular schools in terms of both structure and function. 3. The direction of integrated Arabic language learning is overseen by the headmaster and principal. 4. The control of integrated Arabic language learning includes the monitoring and assessment of language programs within Pesantren and classroom settings. Keywords: Learning; Management; Integrative; Arabic; Language.   Referensi Ahmad Barizi. (2011). Pendidikan Integratif (1 ed., Vol. 32, Nomor 3). UIN Maliki Press. Amrullah, A. F. (2021). Manajemen Kurikulum Pembelajaran Bahasa Arab. In Academia.Edu (hal. 172). Prenada Media. https://www.academia.edu/download/81097305/MANAJEMEN_KURIKULUM_PEMBELAJARAN.pdf Azis, A. (2021). Pembelajaran Bahasa Arab Di Pesantren (Y. A. Azis (ed.); 1 ed.). Sanabil. Budi, C. (2018). Manajemen Pembelajaran (1 ed.). Unnes Press. Creswell, J. W. (1998). QUALITATIVE INQUIRY ANO RESEARCH DESIGN (1 ed.). SAGE Publications. Durroh, U. M. (2009). Approach to Management. The Diabetes Educator, 16(5), 401–406. https://doi.org/10.1177/014572179001600513 Erma Widiana, M. (2021). BUKU AJAR manajemen. In FEBS Letters (Vol. 185, Nomor 1). George R. Terry. (2013). Dasar Dasar Manejemen. https://repository.widyatama.ac.id/xmlui/bitstream/handle/123456789/6350/Bab 2.pdf?sequence=11 Hartini, Acai Sudirman, A. W. (2021). Digitalisasi Human Resources. In H. F. Ningrum (Ed.), e – Jurnal Riset Manajemen (1 ed., Vol. 07, Nomor July). Media Sains Indonesia. Nasarudin. (2022). Kurikulum Pembelajaran Bahasa Arab : Implementasi dalam Mencapai Mutu. 1(June), 1–232. Nur Fadhilah, F., & Sunan Kalijaga Yogyakarta, U. (2023). Manajemen Kurikulum Bahasa Arab di Pesantren Manba’ul ’Ulum Ihtimam: Jurnal Pendidikan Bahasa Arab (Vol. 6, Nomor 1). Pradi Khusufi Syamsu, D. jannah. (2023). Teori Pembelajaran Bahasa Arab Integratif Di Perguruan Tinggi. El-Ibtikar, 12(1). http://repository.radenintan.ac.id/11375/1/PERPUS PUSAT.pdf%0Ahttp://business-law.binus.ac.id/2015/10/08/pariwisata-syariah/%0Ahttps://www.ptonline.com/articles/how-to-get-better-mfi-results%0Ahttps://journal.uir.ac.id/index.php/kiat/article/view/8839 Purnomo, H. (2017). Manajemen Pendidikan Pondok Pesantren (1 ed.). Bildung Pustaka Utama. Syafaruddin, & Nasution, I. (2005). Manajemen Pembelajaran.Pdf (1 ed.). Quantum Teaching. http://repository.uinsu.ac.id/2424/1/manajemen pembelajaran.pdf Talqis, N. (2020). Kompetensi Dasar Pembelajaran Bahasa Arab. In Yogyakarta: Zahir Publishing. Trisnantari, H. E., Mutohar, P. M., & Subiyantoro, H. (2015). Manajemen Pembelajaran Berbasis Kompetensi dan Karakter Bangsa (A. E. Sujianto (ed.); 1 ed.). Cahaya Abadi. Wijaya, M. (2017). Manajemen Pembelajaran Bahasa Arab Sinergi Teori Dan Praktek. Al-Tanzim, 1(1). Wiji Hidayati, Syaefudin, U. M. (2019). Managemen Kurikulum Dan Program Pendidikan (1 ed.). Semesta Aksara. Zaini, M. (2020). Manajemen Kurikulum Terintegrasi (1 ed.). Pustaka Ilmu. Zaini, M. (2021). Media Pembelajaran: Kajian Teoritis dan Praktis (Subakri (ed.); 1 ed.). IAIN Jember Press. الفوزان, ع. ا. ب. إ. (2011). ، اضاءات لرفع كفاءة معلمي اللغة لغير الناطقين بها (1 ed.). مكتبة لسان العرب. عيسى, آ. م. (2018). الإدارة التربوية والتعليمية الحديثة (1 ed., hal. 210). دار ابن النفيس.